(untitled) (Baghdad Science Journal, 2007)
The study includes the epipelic algae in Hemren reservoir, for the period between Januarys to October 2000 .The samples were collected from three selected sites at north, middle and south of reservoir. A total of 96 taxa of epipelic algae were identified. The diatoms were the dominated by 82 taxa represented 85.4% of the total identified species, followed by blue-green algae (cyanophyta) of 6.3 taxa (6%), and then green algae (chlorophyta) of 5.2 taxa (5%). One species was recorded for each crysophyta, euglenophyta and pyrrophyta. The seasonal variation for the cell density showed two peaks during spring and autumn seasons. Few species were dominated during the most studied period such as Achnanthes minutissima, Navicula cryptocephala, N. cryptocephala var . veneta and Nitzschia palea .